The effect of Broussonetia papyrifera silage on intestinal health indicators and fecal bacterial composition in Kazakh sheep - Zheng, Xiaokai; Sun, Yingchao; Guo, Sijin; Yu, Junyang; Huang, Rongzheng; Zhang, Fanfan (Frontiers in Veterinary Science, 2025)
Hybrid Broussonetia papyrifera shows great promise for use in antibiotic-free feed, potentially contributing to the green and sustainable development of the animal husbandry industry. In this study, we investigated the impact of Broussonetia papyrifera silage on the intestinal health of Kazakh sheep. Forty healthy male Kazakh sheep, aged 5 months and weighing an average of 28.28 ± 1.14 kg, were randomly assigned to either a control or an experimental group, each comprising four replicates, with five sheep per replicate. The control group was fed a basal diet, while the experimental group received a diet supplemented with 20% Broussonetia papyrifera silage (dry matter basis). The 70-day experiment included a 10-day adaptation phase followed by a 60-day feeding trial. The results showed that there was no significant difference in growth performance or apparent nutrient digestibility between the experimental and control groups (p > 0.05). However, the experimental group exhibited significantly greater total antioxidant capacity, alongside higher contents of superoxide dismutase, catalase, glutathione peroxidase, immunoglobulins A, M, and G, and interleukins-2, −6, and −8 in the intestinal mucosa; in contrast, malondialdehyde and interleukin-4 contents were significantly reduced (p < 0.01). Furthermore, the dietary inclusion of Broussonetia papyrifera silage resulted in a reduction in the relative abundance of the bacterial genera Turicibacter and Romboutsia (p < 0.05). In conclusion, the feeding of Broussonetia papyrifera silage to Kazakh sheep significantly enhanced immune function, increased antioxidant capacity, and reduced the relative abundance of potentially pathogenic bacteria in the sheep without negatively impacting their growth or nutrient digestion, thus supporting the overall health of the animals.